2012
DOI: 10.1074/jbc.m112.413047
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain-containing Protein 4 (BRD4) Regulates RNA Polymerase II Serine 2 Phosphorylation in Human CD4+ T Cells

Abstract: Background: BRD4 interacts with P-TEFb, which regulates Pol II elongation. Results: Disruption of BRD4 binding by JQ1 resulted in reduced Pol II Ser-2 in CD4ϩ T cells. Conclusion: BRD4 affects Pol II Ser-2 phosphorylation at a subset of lineage-specific active genes in primary human CD4ϩ T cells. Significance: BRD4 binding may represent a means of identifying active promoters and lineage-specific enhancer elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
161
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 44 publications
(49 reference statements)
16
161
0
Order By: Relevance
“…The profile of ongoing transcription (GRO-seq) from normal breast epithelia (MCF10A) (Kim et al 2013) and fetal lung fibroblast (IMR90) (Core et al 2008), and ChIP-seq for serine-5 phosphorylated Pol II from CD4+ T-cells (Zhang et al 2012) was examined at CGI-associated promoters using the same sort order (distance from the TSS to the 3 ′ CGI edge) and class distinctions derived for MCF7 cells in Figure 1C. Interestingly, the position of the dominant pause for individual genes was consistent across multiple cell types (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The profile of ongoing transcription (GRO-seq) from normal breast epithelia (MCF10A) (Kim et al 2013) and fetal lung fibroblast (IMR90) (Core et al 2008), and ChIP-seq for serine-5 phosphorylated Pol II from CD4+ T-cells (Zhang et al 2012) was examined at CGI-associated promoters using the same sort order (distance from the TSS to the 3 ′ CGI edge) and class distinctions derived for MCF7 cells in Figure 1C. Interestingly, the position of the dominant pause for individual genes was consistent across multiple cell types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For MCF10A cells, the following data set was used: GRO-seq (ERX016683) (Kim et al 2013). For CD4+ T cells, the following data sets were used: ChIP-seq of Pol IIS5 (GSM1022949) (Zhang et al 2012) and BRD4 (GSM823378) (Zhang et al 2012). For HeLa cells, the following data sets were used: ChIP-seq of NELFA (GSM1280296) ) and the SUPT5H component of DSIF (GSM1280295) .…”
Section: Data Sets Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similar to other bromodomain proteins, such as BRD2 and BRD3, BRD4 has also been shown to associate with chromatin via interaction with different histone acetylation marks, such as H4K5, H4K8, H4K12, H3K9, H3K14, H4K16, and H3K27. [13][14][15][16][17] Of these, BRD4 bound H3K27Ac sites have been associated with very high gene activity. 16 Emerging data links disruption of super-enhancers with inhibitory oncogene transcription that often exhibits high levels of BRD4 occupancy at nearby enhancer/ super-enhancer regions, such as c-Myc in haematopoietic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…1). 15 Control regions were chosen as 5000 base pair (bp) upstream and downstream of the putative c-Myc super-enhancer region. It has been shown that super-enhancers are correlated with higher levels of occupancy of both H3K27Ac and BRD4.…”
Section: Introductionmentioning
confidence: 99%